How to prepare Chinese-born nurses to care for patients at the end-of-life in Western settings: A discussion paper. Issue 5 (October 2022) - Zheng, Ruishuang; Guo, Qiaohong; Lee, Susan F; Bloomer, Melissa J
Abstract: Background: As a result of globalisation, many Chinese-born nurses choose to work outside China. They are expected to be competent in providing end-of-life care and dealing with dying and death within the new country, where cultural beliefs, attitudes, and values towards dying and death may differ from their own. It is essential to consider the influence of Chinese culture on nurses' confidence and preparedness for end-of-life care, especially for dealing with dying and death. Purpose: To discuss Chinese perspectives on dying and death, and death education and training in mainland China, from which we propose recommendations for nurse educators, clinical mentors and researchers in Western settings on how to prepare Chinese-born nurses to care for patients at end-of-life. Discussion: Chinese-born nurses likely encounter significant cultural challenges when providing end-of-life care to dying patients in Western settings. Chinese-born nurses' perspectives, attitudes and values toward dying and death are shaped by Chinese cultural and social beliefs, practices and expectations, which contrast with those of Western settings. Nurse educators, clinical mentors and researchers in Western settings are encouraged to support and guide Chinese-born nurses in building their cross-cultural understanding and world view to an international view of nursing; essential foundations to the provision of end-of-life care, and nurse coping with dying and death in Western settings. Conclusion: The development of death education programs and training to support Chinese-born nurses to attain their cultural competence is a priority in Western countries, to better promote these nurses' competency in providing high-quality end-of-life care.